A review on recent advances of Protein-Polymer hydrogels. (5th January 2022) - Tang, Yuanhan; Zhang, Xin; Li, Xinyue; Ma, Chiyue; Chu, Xiaoxiao; Wang, Linlin; Xu, Wenlong
Graphical abstract: Abstract: Over the past few decades, polymeric hydrogels have gained significant progress in various fields. As the most biochemically and structurally functional macromolecules in biological organisms, proteins have structural and mechanical properties similar to that of natural extracellular matrices (ECM). By combination of polymers with protein, protein-polymer hydrogel can be constructed as biomaterials with diverse properties and possess a wide range of applications. In this review, we summarized the progress of research on protein-polymer hydrogels and introduced the common fabrication methods. The properties of the protein-polymer hydrogels were briefly described, including biocompatibility, adhesion properties, responsiveness, mechanical properties, swelling properties, and degradability. In addition, we also reviewed the applications of protein-polymer hydrogels in tissue engineering, drug delivery and encapsulation, wearable sensors, adsorption, and other applications. Finally, we summarize the research on protein-polymer hydrogels and highlight the current challenges and future prospects of the field, which may provide a meaningful reference for the field of protein-polymer hydrogels.